2014
DOI: 10.1039/c4ra05576d
|View full text |Cite
|
Sign up to set email alerts
|

The temperature-dependence of the structure-directing effect of 2-methylpiperazine in the synthesis of open-framework aluminophosphates

Abstract: The heating temperature can affect the crystallization process of the initial mixture and the structure-directing effect of 2-methylpiperazine by altering its structure, changing the equilibrium of the reactions, and modifying the assembly of the building oligomers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…42,43 It is well acknowledged that the crystallization temperature has a great inuence on the zeolite nucleation and growth rate, which may alter the reaction intermediate/process, and lead to different crystal phases, morphologies, and sizes. [44][45][46][47][48] Synthesis at lower temperature tends to reduce the crystallization rate and achieve nanosized zeolites. 44,47,48 However, although the lowtemperature syntheses have been studied by several groups, 44,[48][49][50][51] very few cases by simply employing low temperature to build ordered hierarchical structures have been achieved.…”
Section: Introductionmentioning
confidence: 99%
“…42,43 It is well acknowledged that the crystallization temperature has a great inuence on the zeolite nucleation and growth rate, which may alter the reaction intermediate/process, and lead to different crystal phases, morphologies, and sizes. [44][45][46][47][48] Synthesis at lower temperature tends to reduce the crystallization rate and achieve nanosized zeolites. 44,47,48 However, although the lowtemperature syntheses have been studied by several groups, 44,[48][49][50][51] very few cases by simply employing low temperature to build ordered hierarchical structures have been achieved.…”
Section: Introductionmentioning
confidence: 99%
“…The present study confirmed that the structure of AP2pip is also synthesis condition-dependent. In the crystallization of APMeP200, a shoulder peak at −29.7 ppm was observed, which was not observed in the crystallization of APMeP200 from the initial mixture with the same composition at 200 °C 29 . This signal can be assigned to the P sites coordinated by four Al atoms via an oxygen bridge.…”
Section: Resultsmentioning
confidence: 83%
“…These phenomena have made the explanation of the template effect or structure-directing role of organic species by calculation of their non-bonding interactions with the final inorganic open-framework less convincing. Although significant efforts have been made in investigating the structure-directing effect 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 , the origin of the structure-directing effect and how the structure-directing agent directs the corresponding structure are not fully understood.…”
mentioning
confidence: 99%
“…Recently, a series of work concerning the crystallization mechanism of open-framework aluminophosphates and the structure-directing effect in the crystallization of such materials have been reported. [15][16][17][18][19] The investigations demonstrate once again that the crystallization of inorganic microporous materials is a very complicated process. Even though the structure-directing effect of a template is the most important key for the formation of an open-framework structure, there are still many other factors that can change the reaction results, such as the solvent or the other additives.…”
Section: Introductionmentioning
confidence: 96%